COMPARATIVE ANALYSIS OF NOISE, EMISSION, AND PERFORMANCE OF SHIJIRO RACING EXHAUST WITH STANDARD EXHAUST ON A 2020 VESPA SPRINT 150 I-GET - Sutisna, Nanang Ali; Ramadhan, Ibnu Abil (ROTASI, 2025)
This article presents a comprehensive comparative study of the standard and Shijiro Standard Racing exhaust systems on a 2020 Vespa Sprint 150 i-GET. This study aims to evaluate the efficacy of the exhaust system. The research objectives include a comparison of motorcycle performance, noise production and exhaust emissions, with adjustments made in accordance with Indonesian laws and regulations. The study also examines the airflow of the exhaust gas using Computational Fluid Dynamics (CFD) simulations. Testing procedures were conducted on the 2020 Vespa Sprint 150 i-GET, utilizing both standard and racing exhaust systems. These tests included performance, noise, and emission tests, conducted using a dynamometer, decibel meter, and gas analyzer, respectively. The data collected from these tests were analyzed to provide a comprehensive comparison between the standard and racing exhaust systems. The result is that even though it makes a louder sound, the racing exhaust still meets noise regulations in Indonesia. Both exhaust types met emission standards. The performance results revealed that standard exhausts outperformed in horsepower, while racing exhausts excelled in torque. The study also involved the use of reverse engineering to analyze the airflow in the exhaust and obtain design, dimension, and size information. The CFD simulations confirmed the influence of exhaust construction on sound, performance, and emissions. This research provides valuable insights into the performance of standard and Shijiro standard racing exhaust systems, contributing to the body of knowledge in this field.